Hydrogen-assisted combustion dynamics and thermal uniformity in a mini turbojet: Insights from EDM and NPC model - Muslu, Altug; Ogut, Berkay; Karaca, Goktug; Ozkan, Dogus (ELSEVIER SCI LTD, 2026)
Mini turbojet engines are gaining increasing attention for UAV and target-drone propulsion; however, the combined influence of hydrogen enrichment and combustion-model selection on their thermal, aerodynamic, and emission characteristics remains insufficiently understood. This study numerically investigates a mini turbojet combustor operating with hydrogen-kerosene co-combustion fuel blends (0-100% H-2, in 10% increments) using Computational Fluid Dynamics (CFD). Two combustion models- Eddy Dissipation Combustion Model (EDM) and Non-Premixed/Flamelet Combustion Model (NPC) -were compared under a realizable k-epsilon turbulence closure, Discrete Ordinates radiation, and a Chemkin-based H-2-kerosene reaction mechanism. A 1/6 periodic sector with a polyhedral mesh (approximate to 3.2 & times; 10(5) elements) was used to ensure computational efficiency while preserving near-wall resolution. Results show that hydrogen enrichment increases the average outlet temperature from approximately 1250 K (0% H-2) to 1950-2100 K (100% H-2) and enhances gross thrust from approximate to 210 N to over 400 N. The NPC model predicts smoother, more axisymmetric flame structures and lower peak temperatures (approximate to 2160-2500 K), yielding improved outlet temperature uniformity and reduced thermal gradients on turbine blades downstream of the stator compared to the EDM. Conversely, EDM tends to overpredict local heat release at high hydrogen fractions due to its mixing-controlled formulation. Both models reveal that 40-60% hydrogen provides an optimal trade-off between thrust, temperature uniformity, and emission performance. Overall, the findings highlight that detailed chemistry modeling NPC is essential for accurate prediction of hydrogen-kerosene co-combustion in mini turbojet engines, offering valuable insights for the design of low-emission, hydrogen-assisted propulsion systems.
Keywords: Hydrogen-kerosene co-combustion; NPC; EDM; Flame temperature distribution; Outlet temperature uniformity; Thrust performance; INJECTION; EMISSIONS; Energy & Fuels; Engineering